Synaptotagmin 1 Is Involved in Neuropathic Pain and Electroacupuncture-Mediated Analgesic Effect - Juan Wan (International Journal of Molecular Sciences, 2020)
Numerous studies have verified that electroacupuncture (EA) can relieve neuropathic pain through a variety of mechanisms. Synaptotagmin 1 (Syt-1), a synaptic vesicle protein for regulating exocytosis of neurotransmitters, was found to be affected by EA stimulation. However, the roles of Syt-1 in neuropathic pain and EA-induced analgesic effect remain unclear. Here, the effect of Syt-1 on nociception was assessed through an antibody blockade, siRNA silencing, and lentivirus-mediated overexpression of spinal Syt-1 in rats with spared nerve injury (SNI). EA was used for stimulating bilateral “Sanjinjiao” and “Zusanli” acupoints of the SNI rats to evaluate its effect on nociceptive thresholds and spinal Syt-1 expression. The mechanically and thermally nociceptive behaviors were assessed with paw withdrawal threshold (PWT) and paw withdrawal latency (PWL) at different temperatures, respectively, at day 0, 7, 8, 14, and 20. Syt-1 mRNA and protein levels were determined with qRT-PCR and Western blot, respectively, and its distribution was observed with the immunohistochemistry method. The results demonstrated Syt-1 antibody blockade and siRNA silencing increased ipsilateral PWTs and PWLs of SNI rats, while Syt-1 overexpression decreased ipsilateral PWTs and PWLs of rats. EA significantly attenuated nociceptive behaviors and down-regulated spinal Syt-1 protein levels (especially in laminae I-II), which were reversed by Syt-1 overexpression. Our findings firstly indicate that Syt-1 is involved in the development of neuropathic pain and that EA attenuates neuropathic pain, probably through suppressing Syt-1 protein expression in the spinal cord.